Islamic Legal Approaches to Da'wah on Social Media: A Comparative Study of MUI, NU, and Muhammadiyah in Contemporary Indonesia - Sultan, Nurul Lutfiah (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2023)
The purpose of this study is to examine the methodologies employed by three leading Islamic organizations in Indonesia—Majelis Ulama Indonesia (MUI), Nahdlatul Ulama (NU), and Muhammadiyah—in formulating legal and ethical guidelines for da‘wah on social media. In an era where digital platforms play a crucial role in religious communication, the study seeks to understand how these organizations address contemporary challenges such as misinformation, radicalism, ethical dilemmas, and the commercialization of religious messages. Methodologically, this research adopts a qualitative approach with a literature review design, drawing on scholarly studies, official fatwas, organizational documents, and related academic discussions. The analysis compares the interpretive frameworks and decision-making processes of MUI, NU, and Muhammadiyah to highlight both differences and commonalities in their approaches to digital da‘wah. The results indicate that MUI emphasizes a normative-legal orientation through fatwas and formal guidelines, NU integrates cultural traditions and fiqh principles with inclusivity and moderation, and Muhammadiyah advances a rational and progressive method grounded in tajdīd (renewal) and scientific reasoning. These methodological differences influence the strategies of each organization, shaping the diversity of content and audiences in the digital sphere. The originality of this study lies in its comparative perspective, which systematically juxtaposes the methodological orientations of the three organizations within the context of digital da‘wah. While existing studies often focus on one organization, this research highlights how their combined presence enriches Islamic discourse online. The implications suggest that recognizing these methodological diversities can enhance the effectiveness, inclusivity, and ethical integrity of da‘wah in the digital age, offering valuable insights for scholars, practitioners, and policymakers engaged in promoting constructive religious communication.